Comparison of the effectiveness of planned and «on-demand» relaparotomies in patients with secondary diffuse peritonitis (review of literature) - B. V. Sigua; V. P. Zemlyanoy; P. A. Kotkov; V. A. Ignatenko (Вестник хирургии имени И.И. Грекова, 2022)
INTRODUCTION. The main component of the treatment of patients with secondary diffuse peritonitis is surgical intervention aimed at controlling the source of infection. In some cases, a single intervention is not enough for effective sanation of the abdominal cavity, which requires relaparotomy. There is currently no generally accepted approach to the timing and order for such interventions. The OBJECTIVE was to carry out a comparative analysis of the immediate results of patients with secondary diffuse peritonitis treatment using strategies of planned and «on-demand» relaparotomies.METHODS AND MATERIALS. The inclusion criteria for the review were randomized and cohort controlled trials comparing the efficacy of planned and «on-demand» relaparotomies in the treatment of secondary diffuse peritonitis. Primary sources comparing the results of these surgical strategies in adult patients were searched using the CENTRAL, MEDLINE, Scopus and eLibrary databases. The studies were independently assessed for inclusion by two review authors according to the stated eligibility criteria followed by data extraction. The methodological quality of randomized trials was assessed using the Cochrane tool for assessing the risk of bias, nonrandomized ones – using the Russian version of the Newcastle-Ottawa scale. Arising disagreements were resolved through discussions.RESULTS. The review included one randomized controlled trial according to the inclusion criteria and 16 nonrandomized cohort studies with a total of 3672 participants (1835 and 1837 patients undergoing planned and «on-demand» relaparotomies, respectively). Given the significant statistical heterogeneity of the included studies (χ2=119.2, df=16, p<0.00001, I2=87 %), a random effects model was used to assess the intervention effect: the resulting risk of death ratio was 0.68 (95 % CI 0.42–1.10) in favor of planned relaparotomies. The assessment of the systematic review sensitivity, performed by changing the inclusion criteria, showed a similar conclusion: the risk of death ratio was 0.79 in favor of the planned relaparotomies (95 % CI 0.46–1.36).CONCLUSION. The obtained data demonstrated the presence of a statistically insignificant (p=0.11) decrease in postoperative mortality rate in the subgroup of patients with planned relaparotomies. Given the average risk of systematic and significant risk of publication bias in the included studies, these conclusions should be accepted with caution. Further studies in the format of randomized trials will undoubtedly increase the level of the evidence reliability.